What are the benefits and risks of aspirin as primary prophylaxis for CAD events?. Issue 4 (April 2017) - Boswell, Christopher L.; Billings, Thomas A.; Angstman, Kurt B.
Abstract : EVIDENCE‐BASED ANSWER : Aspirin decreases the risk of nonfatal myocardial infarction (MI) by 6 per 1, 000 patients over 10 years for patients at low cardiovascular (CV) risk and by 31 per 1, 000 patients over 10 years for patients at high CV risk. Aspirin also decreases the risk of cardiovascular disease (CVD) events (a composite of CV death, MI, and stroke), but has no significant effect on stroke, CVD mortality, all‐cause mortality, or composite of nonfatal and fatal MI and death due to coronary artery disease (CAD). Aspirin increases major gastrointestinal (GI) and extracranial bleeding events by 4 per 1, 000 patients over 10 years for patients at low CV risk and 22 per 1, 000 patients over 10 years for patients at high risk (SOR: A, meta‐analyses of high‐quality RCTs). The excess risk of any GI bleeding or perforation in aspirin users versus nonusers is about 5 per 1, 000 patients per year but increases up to 20 per 1, 000 patients per year in patients with GI risk factors (SOR: B, case‐control study).